Reduction of inter-observer variability using MRI and CT fusion in delineating of primary tumor for radiotherapy in lung cancer with atelectasis - Zhang, Hongjiao; Fu, Chengrui; Fan, Min; Lu, Liyong; Chen, Yiru; Liu, Chengxin; Sun, Hongfu; Zhao, Qian; Han, Dan; Li, Baosheng; Huang, Wei (Frontiers in Oncology, 2022)
Purpose To compare the difference between magnetic resonance imaging (MRI) and computed tomography (CT)[ Abbreviations：CT: Computed tomography; GTV: Gross tumor volume; MRI: Magnetic resonance imaging; TE: Echo time; TR: Repetition time; T1WI: WATER:BH AX LAVA-Flex; T1WI+C: WATER:BH AX LAVA-Flex-C; T1WI+C Delay : WATER:BH AX LAVA-Flex-C delay; T1WI+C 10 minutes:WATER:BH AX LAVA-Flex-C 10min; T2WI:RTr Ax T2 fs Propeller; CI: Consistence index; DC: Dice coefficient ; NTCP: Normal tissue complication probability] in delineating the target area of lung cancer with atelectasis. Method Retrospective analysis was performed on 15 patients with lung cancer accompanied by atelectasis. All positioning images were transferred to Eclipses' Treatment Planning Systems (TPS). Six MRI sequences (T1WI, T1WI+C, T1WI+C Delay, T1WI+C 10 minutes, T2WI, DWI) were registered with the positioning CT. Five radiation oncologists delineate tumor boundary to obtain the gross tumor volume (GTV). Consistence index (CI) and dice coefficient (DC) were used to measure differences among observers. Results The differences of delineation mean volumes, CI and DC among CT and MRIs were significant. Multiple comparisons were made between MRI sequences and CT. Among them, DWI, T2WI and T1WI + C 10 minutes sequences were statistically significant with CT in mean volumes, DC and CI. The mean volume of DWI, T2WI, T1WI + c 10 minutes sequence in the target area is significantly smaller than that on CT sequence, but the consistency is higher than that of CT sequences. Conclusions The recognition of atelectasis by MRI was better than that by CT, which could reduce inter-observer variability of primary tumor delineation in lung cancer with atelectasis. Among them, DWI, T2WI, T1WI+C 10 minutes may be a better choice to improve the GTV delineation of lung cancer patients with atelectasis.